Societal geo-innovation : selected papers of the 20th AGILE conference on Geographic Information Science - Bregt, Arnold; Sarjakoski, Tapani; Lammeren, Ron van; Rip, Frans (Springer, 2017)
This book contains the full research papers presented at the 20th AGILE Conference on Geographic Information Science, held in 2017 at Wageningen University & Research in Wageningen, the Netherlands. The selected contributions show trends in the domain of geographic information science directed to spatio-temporal perception and spatio-temporal analysis. For that reason the book is also of interest to professionals and researchers in fields outside geographic information science, in which the application of geoinformation could be instrumental in sparking societal innovation.
Keywords: Geographic information systems -- Congresses.; elektronické knihy; electronic books